2019
DOI: 10.1039/c9cc05638f
|View full text |Cite
|
Sign up to set email alerts
|

Inverting the reactivity of troponoid systems in enantioselective higher-order cycloaddition

Abstract: The first enantioselective higher-order cycloaddition involving a tropone derivative that acts as an electron-rich 8π-component is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…An aminocatalytic [8 + 2]cycloaddition employing α,β-unsaturated aldehydes and the inherently unstable tropothione has recently been disclosed. 53 Isobenzofulvenes (IBFs), while less studied, also display a propensity to react as an 8π-component (this may also be considered a 4π-component if the fused benzo is not included in the electron count, but it does indeed experience bonding changes in the reaction). Hafner and Bauer reported the first synthesis of a dimethylamino-IBF derivative and its subsequent reaction with maleic anhydride in both [8 + 2]-and [10 + 2]fashions.…”
Section: [8 + 2]-and [10 + 4]-cycloadditionsmentioning
confidence: 99%
“…An aminocatalytic [8 + 2]cycloaddition employing α,β-unsaturated aldehydes and the inherently unstable tropothione has recently been disclosed. 53 Isobenzofulvenes (IBFs), while less studied, also display a propensity to react as an 8π-component (this may also be considered a 4π-component if the fused benzo is not included in the electron count, but it does indeed experience bonding changes in the reaction). Hafner and Bauer reported the first synthesis of a dimethylamino-IBF derivative and its subsequent reaction with maleic anhydride in both [8 + 2]-and [10 + 2]fashions.…”
Section: [8 + 2]-and [10 + 4]-cycloadditionsmentioning
confidence: 99%
“…Very recently, tropothione 82 was employed as a hetero‐tetraene in the organocatalytic, enantioselective higher‐order cycloaddition for the first time (Scheme ) . Inspired by the work of Machiguchi, it was demonstrated that by introduction of the sulfur atom into the structure of tropone, its electronic properties are modified, making it reactive with its HOMO.…”
Section: Troponoid Systems In Organocatalytic Higher‐order Cycloadditmentioning
confidence: 99%
“…Very recently,t ropothione 82 was employeda sahetero-tetraene in the organocatalytic, enantioselective higher-order cycloaddition fort he first time (Scheme 23). [31] Inspired by the work of Machiguchi, [32] it was demonstrated that by introduction of the sulfur atom into the structure of tropone, its electronic properties are modified, making it reactivew ith its HOMO.A saconsequence, LUMO-lowering aminocatalytic activation strategy was employed for the first time in higher-order cycloadditions, thus inverting the commonr eactivity scheme. Iminium ions 84 derived from the a,b-unsaturateda ldehydes 54 and aminocatalyst 4g were identified as suitable tetraenophiles for this cycloaddition providing [8+ +2]-cycloadducts in ap eriselective fashion.…”
Section: Troponoid Systems In Organocatalytic Higher-order Cycloadditmentioning
confidence: 99%
“…The construction of structurally complex molecular scaffolds traditionally relies on long synthetic sequences to ensure selective transformations. In recent years, organocatalytic higher-order cycloadditions have emerged as efficient tools for the controlled formation of complex cyclic systems in a single synthetic step. Through catalytic generation, inherently unstable π-components of extended conjugation can be wielded under ambient conditions, and their utilization in cycloaddition chemistry can provide products which are unobtainable through traditional Diels–Alder processes. Specifically, strategies involving catalytic dearomatization to access reactive π-systems have recently been employed. The development of such unorthodox cycloaddends expands the range of compounds accessible through cycloaddition chemistry.…”
Section: Introductionmentioning
confidence: 99%